Climate change and women's health: Turning leadership into action. Issue 2 (20th November 2022) - Conry, Jeanne; Robson, Steve
Abstract: Climate change is considered the greatest long‐term challenge we face, and it comes with a direct impact on women's health and pregnancy outcomes. There are many balances that physicians make in deciding elements of care, but environmental impact has not been a consideration. Health care leaders must recognize the impact of their decisions on carbon footprints and creatively look towards changes that will improve global conditions. Synopsis: Climate change is a threat to health, with women and babies as the greatest at risk. We list actions that our profession can take to affect change.